Strengthening Pancasila Character in MI Nurul Iman Dempok Students through Contextual Habituation Based on ABCD - Najmuddin Maya'ba; Rifa Nurmilah; Bentar Candra Perdana; Ikhlashotul A’maliyyah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Abstract: This community service program was conducted at MI Nurul Iman Dempok, Jombang Regency, to strengthen teachers' capacity in implementing contextual habituation-based Civic Education (PPKn) learning for character development. The program addressed three major issues: the limited internalization of Pancasila values in classroom practices, the absence of a structured character habituation system, and teachers' limited competence in utilizing interactive digital learning media. A participatory approach based on the Asset-Based Community Development (ABCD) framework was employed through needs assessment, workshops, mentoring, classroom implementation, monitoring, and evaluation. The participants consisted of 12 teachers who actively engaged in designing contextual learning modules, interactive digital media, and the Pancasila Character Control Book (BKKP). Program evaluation demonstrated a significant improvement in teachers' competencies, as indicated by the increase in average scores from 58% in the pre-test to 89% in the post-test. Furthermore, the overall satisfaction level of participating teachers reached 96%, indicating that the program effectively addressed the identified needs. The program successfully enhanced teachers' pedagogical capacity to integrate Pancasila values into meaningful learning experiences and established sustainable character education practices within the school environment. Keyword: Community Service; Community-Based Research; Teacher Empowerment; Character Education; Contextual Habituation